The Spiritual Leadership Role of KH. Moh. Hafidh Sibawayhie In Educational Innovation at Nurul Wafa Demung Besuki Situbondo Islamic Boarding School - Arifin, Samsul (Institut Agama Islam Negeri Sorong, 2023)
This study aims to determine the Spiritual Leadership Role of KH. Moh. Hafidh Sibawayhie in terms of 1) curriculum innovation initiatives, 2) human resource development, and 3) development of infrastructure facilities at Nurul Wafa Demung Besuki Situbondo Islamic Boarding School. This research uses a qualitative approach. Semi-participant observation, semi-structured interviews, and documentation carried out data collection techniques. At the same time, data analysis uses the attractive model of Miles Huberman and Saldana with steps: data collection, data condensation, data presentation, and concluding the data validity using triangulation and member check. There are three triangulations used, namely source triangulation and method triangulation. The results showed that: 1) In its goal as one of the Islamic Boarding Schools that prints students who are tafaqquh fiddin, various kinds of curriculum innovations carried out to enrich and as specific support for related pesantren in the process of transmitting Islamic religious knowledge treasures at the Nurul Wafa Demung Besuki Situbondo Islamic Boarding School; 2) Factors that encourage KH. Moh. Hafidh Sibawayhie in human resource development at Nurul Wafa Demung Besuki Situbondo Islamic Boarding School is to produce a generation that is tafaqquh fiddin, to provide knowledge and insight into the tasks and roles that must be carried out, as well as an effort to improve the quality of human resources in Nurul Wafa Islamic Boarding School so that pesantren can continue to exist amid society; and 3) Breakthroughs made by KH. Moh. Hafidh Sibawayhie in the development of infrastructure facilities is carried out thoroughly and gradually following the needs of pesantren as Islamic educational institutions. This can be seen from the various construction, addition, and rehabilitation of buildings in the pesantren environment in the context of education for Nurul Wafa Demung Besuki Situbondo Islamic Boarding School students.